IMPLIKASI KOMUNIKASI FATIK DALAM MENINGKATKAN PEMBELAJARAN DI IAIN SALATIGA - Yusuf, Muhamad Fahrudin (Universitas Islam Negeri Raden Intan Lampung, 2019)
This article is the result of a research which is based on various cases of phatic communication invarious contexts, namely, industrial context, social relation context, multicultural society context,and educational context. This is a qualitative study using a case study approach. The aim of thisresearch is to describe and analyze the implications of phatic communication in improvinglearning at IAIN Salatiga. Techniques of collecting data used in this research are focused groupdiscussion (FGD), interview and observation. The research findings show that phaticcommunication between lecturer and student at IAIN Salatiga is well established in the form ofgreeting, nodding, shaking hands with kissing hands, ringing motorcycle horns while nodding head.Phatic communication also has implications in improving learning for students in all departmentsat IAIN Salatiga.